SAT0224 Neopterin – an indicator for lupus activity?. (23rd January 2014) - Zeh, G.; Haas, F.; Schmalzing, M.; Koetter, I.
Abstract : Background: In recent times, the role of Type I and II interferons in pathogenesis as well as in flares of systemic lupus erythematosus has been emphasized. Neopterin is a marker of interferon- induced activation of macrophages and therefore, as it has been shown in several smaller studies, a possible marker of activity in SLE. Objectives: We performed a retrospective analysis of our data which addressed the question of a correlation between neopterin and SLEDAI as well as the complement factors C3 and C4. Methods: Retrospective Analysis of 196 patients with SLE according the revised ACR-criteria of 1982, from our rheumatology outatient clinic since January 1st 2009. We randomly chose one visit of each patient (out of 693 visits totally) in order to avoid statistical bias. The values for SLEDAI, neopterin, C3 and C4 were illustrated graphically and Spearman's correlation coefficient wascalculated. We investigated the correlation between neopterin and SLEDAI, neopterin and C3/C4 as well as for SLEDAI and C3/C4. Patients with chronic kidney disease (GFR <60ml/min) were excluded. Results: We found a weak correlation between SLEDAI and neopterin (Spearman ρ=0, 29; p<0, 001) as well as between C3/C4 and neopterin (ρ= -0, 19 for neopterin/C3; p=0, 0074 and ρ = -0, 087 for neopterin/ C4 respectively; p=0, 2254). In contrast, correlation between SLEDAI and C3 was stronger with ρ= -0, 5 (p<0, 001)and SLEDAI/C4 with ρ= -0, 36 (p<0, 001). Conclusions: Compared with complement factors C3 and C4, we could not find a stronger correlation between neopterin an SLEDAI index in our patients. Neopterin therefore was not superior in estimating Lupus activity in our patients compared with C3 and C4. These data are limited by the fact, that only few patients with high or very high disease activity were included in the calculation. Therefore further investigation in larger patient cohorts is needed. Our results from the largest patient population examined to date lie between those of previous smaller studies which revealed correlation coefficients for neopterin and lupus acitivity indices between 0, 08 and 0, 59. Neopterin may be of value as additional marker of disease activity in individual patients, but generally, the correlation of low C3/C4 with disease activity is better. In our cohort, we had 9 patients with high or very high disease activity (SLEDAI >11). Out of these patients, one had an elevated neopterin and normal values for C3/C4. Disclosure of Interest: None Declared